Prospective investigation of the relationship between dorsal tilt, carpal malalignment, and capitate shift in distal radial fractures. (January 2020) - Dias, Rachel; Johnson, Nick A.; Dias, Joseph J.
Abstract : Aims: Carpal malalignment after a distal radial fracture occurs due to loss of volar tilt. Several studies have shown that this has an adverse influence on function. We aimed to investigate the magnitude of dorsal tilt that leads to carpal malalignment, whether reduction of dorsal tilt will correct carpal malalignment, and which measure of carpal malalignment is the most useful. Methods: Radiographs of patients with a distal radial fracture were prospectively collected and reviewed. Measurements of carpal malalignment were recorded on the initial radiograph, the radiograph following reduction of the fracture, and after a further interval. Linear regression modelling was used to assess the relationship between dorsal tilt and carpal malalignment. Receiver operating characteristic (ROC) analysis was used to identify which values of dorsal tilt led to carpal malalignment. Results: A total of 250 consecutive patients with 252 distal radial fractures were identified. All measures of carpal alignment were significantly associated with dorsal tilt at each timepoint. This relationship persisted after adjustment for age, sex, and the position of the wrist. Capitate shift consistently had the strongest relationship with dorsal tilt and was the only parameter that was not influenced by age or the position of the wrist. ROC curve analysis identified that abnormal capitate shift was seen with > 9° of dorsal tilt. Conclusion: Carpal malalignment is related to dorsal tilt following a distal radial fracture. Reducing the fracture and improving dorsal tilt will reduce carpal malalignment. Capitate shift is easy to assess visually, unrelated to age and sex, and appears to be the most useful measure of carpal malalignment. The aim during reduction of a distal radial fracture should be to realign the capitate with the axis of the radius and prevent carpal malalignment. Cite this article: Bone Joint J 2020;102-B(1):137–143